The membrane characteristics of Plasmodium falciparum-infected and -uninfected heterozygous alpha(0)thalassaemic erythrocytes. - Williams, T; Weatherall, D; Newbold, C (2002)
The alpha thalassaemias are the commonest known human genetic disorders. Although they have almost certainly risen to their current frequencies through natural selection by malaria, the precise mechanism of malaria protection remains unknown. We have investigated the characteristics of red blood cells (RBCs) from individuals heterozygous for alpha(0)thalassaemia (-/alphaalpha) from a range of perspectives. On the basis of the hypothesis that defects in membrane transport could be relevant to the mechanism of malaria protection, we investigated sodium and potassium transport and the activity of the Plamodium falciparum-induced choline channel but found no significant differences in -/alphaalpha RBCs. Using flow cytometry, we found that thalassaemic P. falciparum-infected RBCs (IRBCs) bound 44% more antibody from immune plasma than control IRBCs. This excess binding was abrogated by predigestion of IRBCs with trypsin but was not directed at the variant surface molecule PfEMP1. Furthermore, we found no evidence for altered cytoadhesion of alpha-thalassaemic IRBCs to the endothelial receptors intercellular adhesion molecule-1 (ICAM-1), CD36 or thrombospondin. We hypothesize that altered red-cell membrane band 3 protein may be a target for enhanced antibody binding to alpha-thalassaemic IRBCs and could be involved in the mechanism of malaria protection.